A new approach for the improved interpretation of capacitance measurements for materials utilised in energy storage. Issue 17 (27th February 2015) - Kampouris, Dimitrios K.; Ji, Xiaobo; Randviir, Edward P.; Banks, Craig E.
<x xml:space="preserve">Abstract</x> A simple galvanostatic circuit method that can accurately measure the capacitance of an electrolytic capacitor is reported. The method avoids problems found in current EIS analysis, giving rise to profiles that result in inaccurate derivation of the electrolytic capacitance.